2010
DOI: 10.1029/2009ja014579
|View full text |Cite
|
Sign up to set email alerts
|

Locations of chorus emissions observed by the Polar Plasma Wave Instrument

Abstract: [1] We performed a statistical study of the locations of chorus emissions observed by the Polar spacecraft's Plasma Wave Instrument (PWI) from March 1996 to September 1997, near the minimum of solar cycles 22/23. We examined how the occurrence of chorus emissions in the Polar PWI data set depends upon magnetic local time, magnetic latitude, L shell, and L*. The Polar PWI observed chorus most often over a range of magnetic local times extending from about 2100 MLT around to the dawn flank and into the dayside m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 71 publications
2
25
0
Order By: Relevance
“…Waves on the dayside occur over a wider range of activity, and even during quiet conditions wave mean and time‐averaged amplitudes at noon significantly exceed disturbance amplitudes at midnight (at least at latitudes of >15°). High occurrence in the noon sector is not fully understood [ Tsurutani et al , 2009; Santolík et al , 2010; Sigsbee et al , 2010; Spasojevic and Inan , 2010] but is likely a combination of several factors including higher magnetic field homogeneity and lower damping leading to superior generation or propagation conditions as well as additional contributions to chorus source energy aside from injected electrons. It has been suggested that this could be related to the local magnetospheric configuration because of solar wind speed or dynamic pressure [e.g., Tsurutani and Smith , 1977; Koons and Roeder , 1990; Santolík et al , 2005b; Li et al , 2009; Spasojevic and Inan , 2010].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waves on the dayside occur over a wider range of activity, and even during quiet conditions wave mean and time‐averaged amplitudes at noon significantly exceed disturbance amplitudes at midnight (at least at latitudes of >15°). High occurrence in the noon sector is not fully understood [ Tsurutani et al , 2009; Santolík et al , 2010; Sigsbee et al , 2010; Spasojevic and Inan , 2010] but is likely a combination of several factors including higher magnetic field homogeneity and lower damping leading to superior generation or propagation conditions as well as additional contributions to chorus source energy aside from injected electrons. It has been suggested that this could be related to the local magnetospheric configuration because of solar wind speed or dynamic pressure [e.g., Tsurutani and Smith , 1977; Koons and Roeder , 1990; Santolík et al , 2005b; Li et al , 2009; Spasojevic and Inan , 2010].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Shprits et al [2006] showed that energy and pitch angle diffusion coefficients for pitch angles of 20°–40° for 1 MeV electrons at L = 3.5 can shift from being negligible when considering only equatorially confined waves ( λ < 15°), to ∼10 −5 s −1 (similar to that for pitch angles >40°) by extending waves to just 25° latitude. Studies by Sigsbee et al [2010] and Bunch et al [2011] have begun to address this need and have shown significant chorus occurrence rates and intensities, respectively, in the off‐equatorial region by employing observations from the Plasma Wave Instrument (PWI) onboard the Polar spacecraft, the polar orbit of which (∼18 h, ∼2 × 9 R E , ∼90° inclination, North Pole apogee) has allowed for extension of the known distribution of chorus activity to much higher latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that chorus waves are an important mechanism for energization and loss processes outside the plasmasphere in the outer radiation belt [e.g., Summers et al , 2007]. Chorus waves have been reported to be associated with substorm activity [e.g., Tsurutani and Smith , 1974, 1977]; hence, previous observational chorus wave statistical studies [e.g., Li et al , 2009; Sigsbee et al , 2010; Bunch et al , 2011] were often binned according to the maximum AE value in the previous 3 h ( AE *), magnetic local time ( MLT ), and/or solar wind speed ( V sw ). Due to limitations with SCATHA data, we are unable to bin SC3 data according to MLT or substorm events for a meaningful statistical study.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Though the above estimations are based upon a number of simplified models and thus approximate only, they guide us to tentatively suggest that the ECH be a more promising candidate for higher L shell PsAs as in our event. However, one should be noted that the whistle-mode chorus may well have an off-equatorial source [Tsurutani and Smith, 1977;Sigsbee et al, 2010] which could not be observed by THEMIS satellites. We thus may not entirely exclude, from both theoretical and observational viewpoints, the possible existence of the chorus waves as well as their potential role in generating the observed PsAs in our event.…”
Section: Discussionmentioning
confidence: 99%